Assessment of orthodontic borderline treatment need: A comparison of two aesthetic indices - Ariane Sampson; Neha Passan; Huw G. Jeremiah; Robert Kirschen (SpringerOpen, 2022)
Abstract Objective To compare a new "guide for borderline orthodontic need" (GBON) with the "aesthetic component" (AC) of the IOTN in assessing borderline cases (dental health component DHC 3), and to compare reliability and opinions of orthodontists on the use of each index. Materials and methods Cross-sectional population descriptive study. Ninety-four qualified orthodontists assessed 30 borderline malocclusions according to the GBON and AC indices and completed a questionnaire. Results Kappa analysis showed GBON and AC to have similar intra-examiner reliability (K = 0.64 and 0.60 ,respectively). Cronbach's alpha inter-examiner reliability analysis showed GBON and AC to have similar, acceptable reliability (α = 0.7 and 0.9 ,respectively). There was only fair agreement between GBON and AC in terms of the number of malocclusions deemed as needing treatment (AC threshold 6). Analysis of specific occlusal traits revealed that reverse overjets were deemed as needing treatment according to AC but not anterior open bites. Both traits were assessed as needing treatment according GBON. Despite a lack of familiarity with GBON, assessors found GBON easier to use and more appropriate in assessing borderline malocclusions. Conclusions Both GBON and AC had good and similar inter- and intra-examiner reliability. There was substantial agreement on treatment need between GBON and AC but only when the AC threshold is reduced to 4. GBON was more able to identify malocclusal traits in need of treatment than AC. GBON was found to be easier to use and considered more appropriate than AC in judging DHC 3 malocclusions.